Epidemiology of Malaria in Attapeu Province, Lao PDR in relation to entomological parameters - Vythilingam, I.; Sidavong, B.; Chan, S.T.; Phonemixay, T.; Vanisaveth, V.; Sisoulad, P.; Phetsouvanh, R.; Hakim, S.L.; Phompida, S. (2005)
Surveys were conducted in malaria-endemic villages in the southern province of Attapeu, Lao PDR during various seasons over a 3-year period. All-night mosquito landing collections, blood surveys and a case-control study were conducted. Plasmodium falciparum was the predominant species, and slide positivity rates were higher during the transition/dry season compared with the wet season. Anopheles dirus A was found to be the primary vector, and sporozoite rates were highest during the transition/dry season. Anopheles dirus was found to be endophagic and endophilic. Not using insecticide-treated bed nets, houses close to breeding sites and sleeping away from home were risk factors associated with malaria.